Cbr Values in the Sub-Grade Layer of Reclamation Fill (Case Study: Patimban Port Project Package 6) - Elza Timur Maindah; Herry Hermawan; Aryati indah kusumastuti (Greenation International Journal of Engineering Science, 2026)
Reclamation work on port projects requires embankment materials with adequate bearing capacity, particularly in soaked areas that are saturated with water and potentially subject to soil strength degradation. In the Patimban Port Development Project (Phase 1–2) Package 6: Container Terminal No. 2 Construction, the use of sand as reclamation embankment requires further assessment using the California Bearing Ratio (CBR) parameter to ensure the soil's suitability as a subgrade layer. Variations in soil characteristics due to the layered embankment process and the potential for liquefaction are important factors influencing soil stability. This study aims to determine the suitability of the subgrade layer's CBR value to existing theory, analyze the effect of the reclaimed material's CBR value on subgrade performance, and assess the suitability of the reclaimed soil as a subgrade layer based on CBR technical parameters. The research method used is quantitative with a descriptive approach. Data were obtained through laboratory testing and field testing using Dynamic Cone Penetration (DCP) at 20 test points. The results of the study indicate that: (1) the CBR value of the subgrade layer is in accordance with existing theory, where all values ​​are above the minimum limit of 6% and follow the theoretical pattern in the form of a decrease in the saturated layer and an increase in depth due to overburden pressure; (2) the CBR value of the reclaimed material has a direct effect on subgrade performance, where a lower CBR value in a particular layer becomes a controlling layer that affects the potential for deformation and overall soil stability; and (3) the reclaimed soil meets the technical requirements as a subgrade layer, with CBR values ​​ranging from 8.98% to 22.64% at various depths, making it suitable for use as a supporting layer for construction.